Data Transmission in the X-Ray Emission Frequency Range of Electromagnetic Radiation - G. A. Timofeev; N. N. Potrakhov; A. Yu. Gryaznov (Известия высших учебных заведений России: Радиоэлектроника, 2021)
Introduction.  Data transmission systems using the  X-ray frequency range of electromagnetic radiation  –  X-ray communication system (XCS) have a number of advantages in comparison with radio or optical communication systems. The most significant advantages for practical use are their higher stealth and external interferences resistance, as well as stability against interception and decryption. It is of importance to develop a method for calculating the main parameters of an X-ray communication system: the range and speed of data transmission. In addition, the construction design and results of experimental research of the current X-ray communication system should be provided.Aim.  To develop physical and technical foundations of data transmission systems using the X-ray frequency range of electromagnetic radiation.Materials and methods.  We used an original method of calculating the X-ray emission spectrum, taking into account the attenuation coefficient in the propagation medium.Results.  A technique for data transmission using the X-ray frequency range of electromagnetic radiation was suggested, including a method for calculating basic parameters e.g. the transmission range and speed, as well as the construction design of the current X-ray communication system model. Relations between these parameters and the operating modes of the X-ray tube were shown. The calculated and experimental data were in good agreement, sufficient for practical use. On their basis, it can be expected that at a voltage across the X-ray tube of 200 kV and the tube current of 1A in a 1-μs pulse, data transmission range in free air will be about 250 m. The maximum possible data transmission rate when using the developed X-ray tube will be 5 Mbit/s.Conclusions.  The results of analytical and experimental investigations showed that the range and rate of data transmission of the XCS are exclusively determined by the transmitter energetic capabilities: by voltage and average the X-ray tube current during the generation of packages  (series) of the X-ray pulses, as well as by the duration of a single X-ray pulse. It is concluded that the prospects of XCS depend on the development of specialized X-ray sources generating a series of pulses with the minimum possible duration of every single pulse in a series. Taking into account the specific features, XCS can become an alternative to conventional radio and optical systems for communication and navigation.